Data and reflections on three journalism resarch environments - Machado, Marcia Benetti (Brazilian journalism research, 2005)
The article discusses a parcel of the ﬁ eld of Journalism research in Brazil, focusing on three environments. Firstly, the structure of Graduate programs in Communication Studies and the way this structure is connected to professor research in Graduate courses are presented. Afterwards, there is a mapping of Research Groups at the CNPq (National Council for Scientiﬁ c and Technological Development) Directory. Finally, the production presented over the last ﬁ ve years at the Research Group of Journalism Studies at Compós(National Association of Graduate Programs in Communication) is listed. As an attempt to map the ﬁ eld, this paper proposes categories to visualize, even though temporarily, the complexity and the diversity of Journalism research in the country.